Use of capillary [beta]-hydroxybutyrate for the diagnosis of diabetic ketoacidodis at emergency room : our one-year experieence - Sefedini, Erduan (Array, 2008)
Summary: Diabetic ketoacidosis (DKA) is a life threatening acute complication of diabetes characterized by metabolic derangements caused by an imbalance of glucoregulatory hormones. Ketone bodies (the terminology is traditional, not scientific) as one of the main manifestations are usually tested in urine where their occurrence does not reflect their actual blood levels. Quantitative measurement of the blood ketone bodies (β-hydroxybutyrate) in capillary blood is now available. We conducted a retrospective study by reviewing laboratory data of patients treated at Emergency Room. The primary objective of this study was to assess the relationship between urine ketones and blood ketones. The study included 122 patients. Six patients met the criteria for DKA, whereas the others had either diabetic ketosis or were free from hyperglycemic complications. The main finding of the study was elevation of blood ketones beyond 3.5 mmol/L, which correlated much better with diabetic ketoacidosis than +++ urine ketones. Good correlation between urine ketones and blood ketones was observed at a low concentration of urine ketone bodies